Corporate Taxes and the Location of Intangible Assets Within Multinational Firms - Matthias Dischinger; Nadine Riedel (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
Intangible assets, like patents and trademarks, are increasingly seen as the key to competitive success and as the drivers of corporate profit. Moreover, they constitute a major source of profit shifting opportunities in multinational enterprises (MNEs) due to a highly intransparent transfer pricing process. This paper argues that for both reasons, MNEs have an incentive to locate intangible property at affiliates with a relatively low corporate tax rate. Using panel data on European MNEs and controlling for unobserved time–constant heterogeneity between affiliates, we find that the lower a subsidiary's tax rate relative to other affiliates of the multinational group the higher is its level of intangible asset investment. This effect is statistically and economically significant, even after controlling for subsidiary size and accounting for a dynamic intangible investment pattern.
urn:nbn:de:bvb:19-epub-5294-3
Keywords: H25; F23; H26; C33; 330; multinational enterprise; intangible assets; tax planning; micro level data; Immaterielle Werte; Standortwahl; Multinationales Unternehmen; Unternehmensbesteuerung; Steuerwirkung; Schätzung; Europa